Financial Liberalization and Policy Challenges - Michael P. Dooley (Inter-American Development Bank, Office of the Chief Economist, 1997)
There is growing discontent with the conventional wisdom concerning economic policy. The unhappy fact seems to be that a stable macroeconomic environment may be necessary but not sufficient to coax the desired outcomes from liberalized financial systems. This paper reviews several promising extensions of the conventional model and discusses their policy implications.
Keywords: 330; Finanzmarktregulierung; Schuldenmanagement; Entwicklungsländer